2023
DOI: 10.1097/md.0000000000032914
|View full text |Cite
|
Sign up to set email alerts
|

Successful chemotherapy with continuous immunotherapy for primary pulmonary endovascular epithelioid hemangioendothelioma: A case report

Abstract: Rationale: Epithelioid hemangioendothelioma (EHE) is a rare, low to moderate-grade malignancy, even less in pulmonary endovascular neoplasm. Patients with pulmonary EHE have no optimal treatment, resulting in poor prognoses. Patient concerns: We reported a 42-year-old man with multiple mild metabolic uptakes in pulmonary endovascular filling defect with a maximum standardized uptake value of 4.5 by 18-fluorodeoxyglucose/fibroblast associated protein inhibitor-positron emission tomography/ computed tomography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Other treatments include chemotherapy, radiotherapy, steroids, and low dose interferon has been used in several patients. Very limited clinical trials have been done using chemotherapy and radiotherapy; therefore, the effectiveness of these methods remain unclear 13 . In our case, as the mass was in the left upper lobe, we considered lobectomy to extirpate the lesion completely and that extirpation by VATS might be a better option to treat this condition.…”
Section: Discussionmentioning
confidence: 96%
“…Other treatments include chemotherapy, radiotherapy, steroids, and low dose interferon has been used in several patients. Very limited clinical trials have been done using chemotherapy and radiotherapy; therefore, the effectiveness of these methods remain unclear 13 . In our case, as the mass was in the left upper lobe, we considered lobectomy to extirpate the lesion completely and that extirpation by VATS might be a better option to treat this condition.…”
Section: Discussionmentioning
confidence: 96%
“…It should be noted that some studies have reported that immunotherapy for prostate cancer was not significantly effective ( 31 , 32 ). However, treatments involving pembrolizumab ( 33 ) and toripalimab ( 34 ) have demonstrated benefits in epithelioid hemangioendothelioma, making immunotherapy a viable alternative strategy for patients with widespread metastatic epithelioid hemangioendothelioma. The difference in treatment between the two may be due to the differing pathological types, as well as the low incidence of hemangioendothelioma, resulting in limited data on the immunotherapy research.…”
Section: Discussionmentioning
confidence: 99%
“…Early gene expression studies have provided evidence that PE is reflected by alterations in the whole blood transcriptome correlated with pathological pathways. [9][10][11] The integration of multi-layer biological data enriched with clinical annotations through advanced machine learning now enables the development of highly potent diagnostic tools applicable at the point of care. Prospective studies involving gene expression profiling in larger patient cohorts, functional validations, evaluation in real-world settings, and comparison with current methods are warranted before biomarkers can be confidently applied in clinical practice.…”
Section: Introductionmentioning
confidence: 99%